Determinants of audit report lag: effect of corporate governance in listed companies in the Malaysian construction industry / Syahmi Akmal Kusin and Mohd Halim Kadri - Kusin, Syahmi Akmal; Kadri, Mohd Halim (Accounting Research Institute (ARI), 2020)
Timeliness of audited financial reports is pondered to be a crucial and important factor affecting the usefulness and quality of information that is available to its users. This study examined the effect of corporate governance on audit report lag in listed companies in the Malaysian construction industry. The construction industry in Malaysia is one of the most challenging and dynamic. The Agency Theory is a relevant theory to this study as it explains corporate governance which functions as an oversight mechanism to lessen agency problems. This study particularly examined the effect of board size, board diversity, board meeting, CEO duality, audit committee size and type of auditor on audit report lag. The study collected data covering a three-year period from 2015 to 2017. The study sample comprised of 138 Malaysian listed companies in the sector from Bursa Malaysia. Data were extracted from the annual report of the sample companies that was downloaded from the Bursa Malaysia website. Regression analysis was performed to examine the relationship between corporate governance attributes and audit report lag. The results demonstrated that board size, board diversity and auditor type have a significant relationship with audit report lag. Meanwhile, board meeting, CEO duality and audit committee size do not have a significant relationship with audit report lag. This study contributes to the literature on corporate governance and auditing. Particular explanations of the findings, implications, limitation and recommendation for future research are highlighted.